1993
DOI: 10.1159/000187563
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis-Associated Arthropathy: Secondary Ion Mass Spectrometry Evidence of Aluminum Silicate in <i>β</i><sub>2</sub>-MicroglobuIin Amyloid Synovial Tissue and Articular Cartilage

Abstract: The role of aluminum accumulation in articular tissues of patients affected by dialysis-associated arthropathy (DAA) is questioned. The aim of this work is to identify the nature of these aluminum accumulations by the use of secondary ion mass spectrometry (SIMS). Al/Si ratios of about 1, measured by SIMS, strongly suggest for the first time the presence of aluminum silicates and possibly aluminum hydroxides in amyloid synovial tissue and articular cartilage of 1 patient with DAA and aluminum intoxication. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Because Al is involved in neurodegenerative processes, this is a clinically relevant observation. As has been shown so far, a chronic exposure to Al causes its accumulation in various tissues [45,46,47,48,49,50,51]. It has been proven that even low doses of aluminum are neurotoxic, induce inflammatory processes, and adversely affect cognitive functions and morphological changes in the central nervous system.…”
Section: Resultsmentioning
confidence: 99%
“…Because Al is involved in neurodegenerative processes, this is a clinically relevant observation. As has been shown so far, a chronic exposure to Al causes its accumulation in various tissues [45,46,47,48,49,50,51]. It has been proven that even low doses of aluminum are neurotoxic, induce inflammatory processes, and adversely affect cognitive functions and morphological changes in the central nervous system.…”
Section: Resultsmentioning
confidence: 99%
“…As noted previously, chronic Al exposure can cause the accumulation of AβP, impair spatial learning memory and induce conformational changes to proteins related to neurodegeneration. These include tau, PHF-tau, synuclein, amylin, ABri, microglobulin, and APP [36,37,38,39,40,41]. A recent study reported brain Al levels of subjects suffering from Alzheimer’s disease and multiple sclerosis, the content of which is in excess of 10 and 50 mg/kg, respectively [11].…”
Section: Discussionmentioning
confidence: 99%
“…The daily intake of Al is about 20mg, and silicon absorption has been evaluated at 20–50 mg. Water and other drinks can provide 19% of daily intake [36].…”
Section: Discussionmentioning
confidence: 99%
“…Al has also been reported to bind and cause conformational changes in other AD-related proteins, including APP [138], tau protein [32, 57], and PHF-tau protein [139] and in proteins related to other neurodegenerative diseases such as α -synuclein (Parkinson's disease (PD) and dementia with Lewy bodies; DLB) [140, 141], amylin (diabetes mellitus) [142], ABri (familial British dementia) [143], and ataxin 3 (spinocerebellar ataxia type 3) [144], β 2 -microglobulin (dialysis-related arthropathy) [145] (Table 2). …”
Section: Link Between Al and Admentioning
confidence: 99%